PENGEMBANGAN MODUL PEMBELAJARAN DENGAN MENGGUNAKAN MEDIA WEB BERBASIS APLIKASI LECTORA INSPIRE TYPE 17 PADA MATERI CAHAYA DAN ALAT OPTIK DI SEKOLAH MENENGAH PERTAMA - Tunnisa, Rania; Ma’ruf, Zuhdi; Nor, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The use of learning media is very necessary for the delivery of modules, especially on light modules and optical devices that can explain the concepts virtually. Therefore, the purpose of this study was to produce WEB media based on the Lectora inspire type 17 application on light materials and optical instruments in junior high schools and to determine the validity of the learning modules developed. The research method used is Research and Development (R&D) using the Plomp model which is only limited to 4 stages, namely the Preliminary investigation, design, realization/construction, evaluation, and revision stages. The data was obtained in the form of the average validation results of three validators. The results showed that the average validity of the overall assessment in validation II was 3.5 with a very valid category. So it can be concluded that the learning module using WEB media based on the Lectora inspire type 17 application on light materials and optical devices in junior high schools are categorized as valid and suitable for use as a medium for learning physics in junior high schools.Keywords: Learning Module, Lectora Inspire Type 17, Plomp Model.